Post-war Landscapes - Marcin Lachowski (Miejsce)
This article considers how painterly space was redefined in the work of artists after World War II. Right after the war, when cities were in a state of destruction, the trope of the city in ruins featured prominently in art. A metaphorical approach to ruins can be seen in documentary photographs of devastated Warsaw, the drawings of Tadeusz Kulisiewicz, and the classical paintings of Felicjan Szczęsny Kowarski. Within this spectrum lies a broad range of paintings that portrayed landscape in terms of peril, strangeness, and unrecognizability—landscapes deprived of visual coherence or unity and instead defined by oblivion, fissure, and the abysmal.